Synthesis of carbon nanotube-titanium dioxide photocatalysts via modified sol-gel method for removal of phenol - Mohd. Hatta, Mohd. Hayrie (2015)
In the present study, a series of carbon nanotube-titanium dioxide (CNT-TiO2) has been successfully synthesized by a modified sol-gel method in the presence of acetyl acetone as the chelating ligand. X-ray diffraction (XRD), diffuse reflectance ultravioletvisible spectroscopy (DR UV-Vis), Fourier transforms infrared spectroscopy (FTIR) and scanning electron microscope (SEM) were used to investigate the structural, optical properties and morphology of the sample. XRD patterns demonstrated that the addition of CNT maintained the anatase phase of TiO2, while DR UV-Vis analysis showed the additional absorbance in the visible light region after addition of the CNT, suggesting the successful incorporation of CNT into TiO2. The SEM image revealed the unaffected morphology of TiO2 after addition of the CNT. The photocatalytic removal of phenol was carried out under UV light irradiation at room temperature for 24 hours. It was confirmed that all CNT-TiO2 series showed better adsorption and photocatalytic activity than the TiO2. The best photocatalyst was 5% CNT-TiO2 with 68% of phenol removal, while TiO2 showed only 17% phenol removal. Adsorption process was proposed to be one of the important factors for the high activity. It was concluded that the incorporation of CNT into TiO2 using the modified sol-gel method would be a good alternative method to prepare highly active carbon based-TiO2 photocatalysts.